Quality of Comercial Import Fish Oil (Softgel) in Central Java - Sugeng Heri Suseno; Agoes Mardiono Jacoeb; Hanani Putri Yocinta; Kamini Kamini (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Fish oil is a source of omega-3s, specifically EPA (Eicosapentaenoic acid) and DHA (Docosahexaenoic acid). These fatty acids play an important role for human health. Commercial fish oil production is increasing, but most of the products do not meet IFOS standards. This is a challenge for producers to produce standardized fish oil. The aim of this research was to identify and determining quality of softgel commercial fish oil in Central Java areas based on International Fish Oil Standards (IFOS). The method used was the treatment of differences in the area of origin of commercial fish oil purchases followed by testing the peroxide value, anisidine value, and total oxidation, fatty acid profile, and analysis of free fatty acids. The results showed that the percentage of free fatty acids, peroxide values, anisidine values, and total oxidation values that met IFOS standards were 37 % (3 of 8 samples), 17 % (1 of 8 samples), 83 % (7 of 8 samples) and 50 % (4 out of 8 samples). The best fish oil that fulfil all IFOS parameters has been the sample fish oil E from Tegal. Fish oil D from Tegal has the highest content of omega-3, EPA, and DHA, with valuesof 83.65%, 56.57%, and 26.74% respectively.